The Consumer Protection Efforts through the Inclusion of Non-Halal Information on Food Products - Hamonangan, Josafat; Sakti, Muthia (Law Development Journal, 2024)
Indonesia, the largest Muslim-majority country, requires a substantial amount of food to meet the needs of its population. This research examines efforts to protect consumers through the inclusion of non-halal information on food products. The study focuses on the regulatory framework, including the Consumer Protection Law, Law No. 33 of 2014 on Halal Product Assurance, and relevant regulations in Indonesia. It aims to analyze how including non-halal information contributes to protecting consumer rights concerning food products. Employing a juridical-normative approach, the research utilizes literature review and interviews. The findings underscore the importance of transparency regarding the halal status of products for consumers, with the inclusion of non-halal information serving as a protective measure for consumer rights. It reaffirms the business actor’s responsibility to provide such information on products not meeting halal standards. The study reveals that regulations mandating the inclusion of non-halal information can uphold the right to information for Muslim consumers. Should consumer rights remain unmet, individuals retain the option to seek legal recourse through civil, criminal, and administrative avenues. This research contributes to comprehending consumer protection practices concerning the halal status of food products in Indonesia. It lays the groundwork for policy enhancements and raising producer awareness of consumer rights in the context of halal food products.